Microorganisms grown in urine cultures and antimicrobial resistance patterns: A randomised retrospective analysis from a tertiary hospital - Canan Demir; Salih Metin (Journal of Infection in Developing Countries)
Introduction: Patients in intensive care units (ICU) are 5-7 times more susceptible to infection than other groups, which increases the prevalence of hospital-acquired infections and associated sepsis accounting for 60% of deaths. Gram-negative bacteria are the most common source of urinary tract infections that cause morbidity, mortality, and sepsis in the ICU. The aim of this study is to detect the most commonly grown microorganisms and antibiotic resistance in urine cultures in the intensive care units of our tertiary city hospital, which has more than 20% of the ICU beds in Bursa By this way, we suppose that we will contribute to surveillance studies in our province, our country.